Fish Freshness Indicator for Sensing Fish Quality during Storage - Do-Yeong Kim; Sung-Woo Park; Han-Seung Shin (Foods, 2023)
This study aims to develop a freshness indicator for fish products that changes color to indicate ammonia among volatile base compounds (TVB-N) generated during storage. Through an optimization experiment, we observed the indicator’s color change relative to the ammonia concentration standard, finally selecting cresol red and bromocresol purple for the indicator mixture. In addition, eco-DEHCH and Breathron film were applied to the freshness indicator, considering environmental and economic values. For the storage experiment, Chub mackerel (Scomber japonicus), Spanish mackerel (Scomberomorus niphonius), and Largehead hairtail (Trichiurus lepturus) samples were stored at three different temperatures (4, 10, and 20 °C) for seven days, and we measured pH, TVB-N, total bacterial count, and ammonia content every 24 h. The pH-sensitive sensors’ color changes monitor amine release, especially ammonia, from decomposing fish. The chromatic parameter ∆E value increased significantly with fish product storage periods. We confirmed that when the freshness limit and bacterial spoilage level were reached, the color of the indicator changed from yellow to black and sequentially changed to purple as the storage period increased. Therefore, a developed freshness indicator can be used for determining the quality of fish products quickly and non-destructively by reflecting the freshness and spoilage degree of fish products during storage.